Not all forms of dietary phosphorus are equal: an evaluation of postprandial phosphorus concentrations in the plasma of the cat. Issue 3 (13th November 2018) - Coltherd, Jennifer C.; Staunton, Ruth; Colyer, Alison; Thomas, Gäelle; Gilham, Matthew; Logan, Darren W.; Butterwick, Richard; Watson, Phillip
Abstract: Phosphorus is present in diets as naturally occurring P from raw materials or added as an inorganic salt. However, little is known about postprandial kinetics of P absorption in cats. Here, we describe several studies quantifying postprandial kinetics following the ingestion of diets of varying composition. Briefly, cats were fed a meal consisting of 50 % of their metabolic energy requirement in a randomised crossover design. A pre-meal baseline blood sample was taken via cephalic catheter and repeated measurements taken regularly up to 6 h post-meal to assess the whole blood ionised Ca, plasma P and parathyroid hormone concentrations. A diet containing 4·8 g total P/4184 kJ (1000 kcal), 3·5 g P from sodium dihydrogen phosphate (NaH2 PO4 )/4184 kJ (1000 kcal) and Ca:P 0·6 caused a marked increase in plasma P from baseline to a peak of 1·976 (95% CI 1·724, 2·266) mmol/l ( P <0·001), whereas a diet containing 3·38 g total P/4184 kJ (1000 kcal), no added inorganic P and Ca:P 1·55 resulted in a postprandial decrease in plasma P ( P = 0·008). Subsequent data indicate that added inorganic P salts in the diet above 0·5 g P/4184 kJ (1000 kcal) cause an increase in plasma P in cats, while diets below this do not. The data presented here demonstrate that sources of added inorganic P salts cause a temporary postprandial increase in plasma P in a dose-dependent manner, prolonged in diets with Ca:P <1·0. Dietary P derived from natural food ingredients (e.g. meat or vegetable matter) does not appear to have any effect on postprandial plasma P.